Keefektifan Teknik Drama Segitiga Karpman untuk Meningkatkan Keterampilan Empati Siswa Sekolah Menengah Pertama - Latifah, Leny (Jurnal Kajian Bimbingan dan Konseling, 2019)
Empathic skills encourage an individual to look into the problems more clearly and objectively. Without empathy, it is difficult to know what others are experiencing because it is not possible to feel and understand the conditions of others. The particular study aimed to determine the effectiveness of Karpman drama triangle technique to increase junior high school students’ empathy skill. The research subjects were six students of eighth grade in Sekolah Menengah Pertama Negeri 1 Turen, Malang. The particular research was Quasi-Experiment using the pretest and posttest design. The instruments were student empathy scale; experimental guidelines; and observation guidelines. The study showed that Karpman drama triangle technique was effective to increase junior high school students’ empathy skill.